Implementation of Video Quiz (Educaplay) through Discovery Learning to Improve Learning Outcomes in Narrative Text - Kirana, Khalida -; Basuki, Edi Pujo; Faizah, Nurul (Jurnal Pendidikan Bahasa Inggris Proficiency, 2026)
Low student learning outcomes is problems in English language learning on narrative text material at junior high school level. This study aims to examine the application of video quiz (Educaplay) in the discovery learning model to improve student learning outcomes in narrative text material. This study used a classroom action research design implemented in two cycles on class VIII C students at Khadijah Junior High School. Data were collected using tests and questionnaires. The results showed that the pre-cycle results showed that the average student score was 74.55 with a completeness of 60.61%. After implementing the actions in cycle I, the average score was 79.7- with a learning completeness of 72.73%. Furthermore, improvements were made in cycle II by using more adapted learning models and strategies and more optimal time. In cycle II, the average student score increased to 85.76 with a learning completeness of 84.85%. In addition, the standard deviation also decreased from 21.08 (pre-cycle) and 15.10 (cycle 1) to 12.00 (cycle II), indicating that student learning outcomes were more average than before. Thus, the use of the discovery learning model with video quiz (Educaplay) is effective in improving student learning outcomes in narrative text learning.